Metabolic Crossroad Between Macrophages and Cancer Cells: Overview of Hepatocellular Carcinoma - Anna Santarsiero; Paolo Convertini; Dominga Iacobazzi; Vittoria Infantino; Simona Todisco (Biomedicines)
The metabolic interplay between macrophages and cancer cells mirrors the plasticity of both kinds of cells, which adapt to the microenvironment by sustaining cell growth and proliferation. In this way, cancer cells induce macrophage polarization, and, on the other hand, tumor-associated macrophages (TAMs) contribute to the survival of cancer cells. In a simplified manner, macrophages can assume two opposite subtypes: M1, pro-inflammatory and anti-tumor phenotype, and M2, anti-inflammatory and protumor phenotype. How do cancer cells induce macrophage polarization? Any actor involved in tumor growth, including the mitochondria, releases molecules into the tumor microenvironment (TME) that trigger a subtype transition. These metabolic changes are the primary cause of this polarization. Hepatocellular carcinoma (HCC), the prevalent type of liver primary tumor, is characterized by cells with extensive metabolic adaptions due to high flexibility in different environmental conditions. This review focuses on the main metabolic features of M1 and M2 macrophages and HCC cells underlying their metabolic behavior in response to TME.